2022
DOI: 10.3390/ijms23031227
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy and Multi-Modality Imaging of Up-Conversion Nanomaterial Doped with AuNPs

Abstract: Two key concerns exist in contemporary cancer chemotherapy in clinic: limited therapeutic efficiency and substantial side effects in patients. In recent years, researchers have been investigating a revolutionary cancer treatment technique, and photodynamic therapy (PDT) has been proposed by many scholars. A drug for photodynamic cancer treatment was synthesized using the hydrothermal method, which has a high efficiency to release reactive oxygen species (ROS). It may also be utilized as a clear multi-modality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…According to Zhang et al, the upconversion of Au-doped nanoparticles has a relatively high light intensity. In particular, Au-doped UCNPs are non-toxic to tissues, making them extremely effective ( Zhang et al, 2022 ). In turn, the Tumor Microenvironment (TME)-Responsive nanoparticles group includes such platforms as: nanogels, hybrid micelles, nanocoatings, and miceplexes.…”
Section: Resultsmentioning
confidence: 99%
“…According to Zhang et al, the upconversion of Au-doped nanoparticles has a relatively high light intensity. In particular, Au-doped UCNPs are non-toxic to tissues, making them extremely effective ( Zhang et al, 2022 ). In turn, the Tumor Microenvironment (TME)-Responsive nanoparticles group includes such platforms as: nanogels, hybrid micelles, nanocoatings, and miceplexes.…”
Section: Resultsmentioning
confidence: 99%
“…Their high mobility facilitates easy transport to various organs and effective penetration into targeted regions. Conjugates with therapeutic molecules enable selective drug delivery to diseased tissues, such as cancer cells, and their size is comparable to DNA but significantly smaller than red blood cells [6]. This enhances performance and imparts distinctive physical, chemical, and optical properties, valuable in the medical field for cancer treatment and detection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nanoparticles can function as targeting agents to target specific molecules in cancer cells for better cancer imaging, which can improve cancer diagnosis. Several studies have demonstrated the potential of nanoparticles in enhancing cancer imaging for improved detection [ 2 , 3 ]. Nanomaterials are produced for precise applications in cancer diagnosis and detection and the main objective is to synthesize nanomaterials that are effective and can be easily delivered to cancerous tumor cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%